Immunomodulatory Role of CB2 Receptors in Emotional and Cognitive Disorders - Morcuende, Alvaro; García-Gutiérrez, María Salud; Tambaro, Simone; Nieto, Elena; Manzanares, Jorge; Femenia, Teresa (Frontiers in Psychiatry, 2022)
Emotional behavior, memory, and learning have been associated with alterations in the immune system in neuropsychiatric and neurodegenerative diseases. In recent years, several studies pointed out the involvement of the cannabinoid receptor 2 (CB2r) in the immune system and the regulation of inflammation. This receptor is widely distributed in different tissues and organs with higher expression in spleen and immune system cells. However, CB2r has also been detected in several brain areas and different brain cell types, such as neurons and glia. These findings suggest that CB2r may closely relate the immune system and the brain circuits regulating inflammation, mood, and cognitive functions. Therefore, we review the studies that may help elucidate the molecular bases of CB2r in regulating inflammation in different brain cells and its role in the pathophysiology of psychiatric and neurodegenerative disorders.